2018
DOI: 10.1016/j.reth.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced survival and insulin secretion of insulinoma cell aggregates by incorporating gelatin hydrogel microspheres

Abstract: IntroductionThe objective of this study is to evaluate the survival and glucose-induced insulin secretion of rat-derived insulinoma cells (INS-1) from their aggregates incorporating different size of gelatin hydrogel microspheres comparing with microspheres-free cell aggregates.MethodsThe gelatin hydrogel microspheres were prepared by the conventional w/o emulsion method. The INS-1 cells were cultured in a V-bottomed well, combining with or without the gelatin hydrogel microspheres to form their aggregates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…[26][27][28][29][30] Among the types of carriers, DEB is widely accepted in clinical practice and several brands of DEB have been produced in medical application including DC beads, LC beads, HSM, and CSM, which are made of poly lactic-co-glycolic acid (PLGA), polyvinyl alcohol (PVA), or glucans. 12,13,[31][32][33][34] A previous study illuminates that DC beads achieve 95% doxorubicin-loading efficiency and HSM realizes 100% doxorubicin-loading efficiency, meanwhile, as to CSM, as the first DEB developed in China which mainly made of PVA, is also observed to possess similar doxorubicin loadability. 11,18 However, the application of these DEBs in delivering oxaliplatin is very limited, only 3 studies (1 for noncommercial use beads and 2 for HSM) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] Among the types of carriers, DEB is widely accepted in clinical practice and several brands of DEB have been produced in medical application including DC beads, LC beads, HSM, and CSM, which are made of poly lactic-co-glycolic acid (PLGA), polyvinyl alcohol (PVA), or glucans. 12,13,[31][32][33][34] A previous study illuminates that DC beads achieve 95% doxorubicin-loading efficiency and HSM realizes 100% doxorubicin-loading efficiency, meanwhile, as to CSM, as the first DEB developed in China which mainly made of PVA, is also observed to possess similar doxorubicin loadability. 11,18 However, the application of these DEBs in delivering oxaliplatin is very limited, only 3 studies (1 for noncommercial use beads and 2 for HSM) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We and other groups have reported that the incorporation of gelatin microspheres into spheroids increases oxygen permeability and inhibits cell death in the spheroids. [23][24][25] However, these approaches could not solve the problem of decreasing O 2 concentration under culture conditions. Other groups have used a bioreactor with a large volume of medium for the preparation of spheroids.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity, cost, and time-consuming nature of primary islets of Langerhans research and training motivated our team to create an accessible, rapidly renewable, and representative model system for isolated islets that could be used to train personnel and inform experiments that require valuable primary islets. Previous work by several groups has shown that insulinoma cell lines form islet-like aggregates or IPIs (13)(14)(15)(16)(17)(18)(19)(20)34). However, previous approaches to create IPIs required relatively complex methodology, often with relatively low yields and limited functional characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that engineered and immortalized insulinoma b cell lines were capable of forming cellular aggregations/pseudo-islets, which more closely reflect primary islet morphology (13)(14)(15)(16)(17)(18)(19)(20). Data also have shown that insulinoma-derived pseudo-islets have improved insulin secretory characteristics relative to cells propagated in monolayer culture (14,16,17).…”
Section: Introductionmentioning
confidence: 97%